ENCOURAGING A FLEXIBLE TONGUE (Proceedings of International Educators Conference, 2024)
This presentation highlights innovative pronunciation strategies to practice tongue movements and word stress. Five creative and learner-centered strategies will be explained and practiced with the goal of developing a “flexible tongue” to improve pronunciation ability in beginning and intermediate learners.